Symbolic Regression and Two‐Point Statistics Assisted Structure‐Property Linkage Based on Irregular‐Representative Volume Element. Issue 1 (21st October 2022) - Chen, Yiming; Hu, Xiaobing; Zhao, Jiajun; Wang, Zhijun; Li, Junjie; Wang, Jincheng
Abstract: Quantifying the microstructure of materials is of significance in material development, especially for building the relationship between structure and property. To establish a remarkable structure‐property (SP) linkage, a novel concept referred to as irregular‐representative volume element (IRVE) based on panoramic image stitching technology (PIST) is proposed and a data‐driven scheme integrating irregular domain‐oriented two‐point statistics, principal component analysis (PCA), and symbolic regression based on genetic programming (GPSR) is constructed. Combining with advanced image processing and genetic programming technologies, this scheme improves the microstructure quantization framework. This scheme can not only be applied in different complex conditions for extracting the information of a material microstructure, but can also to embody details of microstructure from the perspective of large scale. IRVE is demonstrated to have both strong statistical representativeness and sufficient physical interpretation, which makes the scheme robust and reliable. Performing the scheme on an example of ferrite heat‐resistant steels, it shows a powerful ability in building an equational SP linkage with high precision ( R = 0.91, RMSE = 13.17), the generalization ability of the linkage is also validated by an unseen steel (relative percentage error is 2.66%). The scheme has bright application prospects in predicting mechanical property and accelerating alloy design. Abstract : A novel IRVE concept for establishing SP linkage based on PIST is proposed and successfully applied to an experimental example of ferrite heat‐resistant steels. A data‐driven scheme integrating IRVE construction method, irregular domain‐oriented RI2SS, PCA and GPSR is also developed to extract the information of a microstructure with different scales of materials.